Do Higher Corporate Taxes Reduce Wages? Micro Evidence from Germany - Fuest, Clemens; Peichl, Andreas; Siegloch, Sebastian (American Economic Review, 2018)
This paper estimates the incidence of corporate taxes on wages using a 20-year panel of German municipalities exploiting 6,800 tax changes for identification. Using event study designs and difference-in-differences models, we find that workers bear about one-half of the total tax burden. Administrative linked employer-employee data allow us to estimate heterogeneous firm and worker effects. Our findings highlight the importance of labor market institutions and profit-shifting opportunities for the incidence of corporate taxes on wages. Moreover, we show that low-skilled, young, and female employees bear a larger share of the tax burden. This has important distributive implications. (JEL H25, H31, H71, J16, J24, J31)